Increased Soluble Urokinase-Type Plasminogen Activator Receptor (suPAR) Levels in Plasma of Suicide Attempters - Ventorp, Filip (PLoS One, 2015)
The soluble form of the urokinase receptor, suPAR, has been suggested as a novel biomarker of low-grade inflammation. Activation of the immune system has been proposed to contribute to the development of depression and suicidal behavior. In order to identify depressed and suicidal individuals who could benefit from an anti-inflammatory treatment, a reliable biomarker of low-grade inflammation is vital. This study evaluates plasma suPAR levels as a biomarker of low-grade inflammation in patients with major depressive disorder and in patients who recently attempted suicide. The plasma suPAR and an established biomarker, C reactive protein (CRP) of suicide attempters (n = 54), depressed patients (n = 19) and healthy controls (n = 19) was analyzed with enzyme-linked immunosorbent assays. The biomarker attributes of sensitivity and sensibility were evaluated using ROC curve analysis. Both the depressed patients and suicide attempters had increased plasma suPAR. The levels of suPAR discriminated better between controls and suicide attempters than did CRP. In the future, plasma suPAR might be a superior prognosticator regarding outcome of treatment applying conventional antidepressants in conjunction with anti-inflammatory drugs.